Blood vessels detection and segmentation in retina using gabor filters - Farokhian, Farnaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Currently, medical images have become an important field of research due to the progress in their acquisition, storage and management in a wide range of applications. In the medical domain, a huge effort has been devoted to develop applications and tools related with disease diagnosis and identification of anatomical structures. Spatially, the extraction of the vessel pattern from retinal images has an important issue not only in the medical tools; but also in biometric identification applications. A lot of research has been devoted to accurately extract the retinal vessels in order to define applications for early ocular disease diagnosis. The main regions of retina are optic disk, fovea and blood vessels. The identification of these areas can help in analyses of the diseases that affect these regions such as retinopathy of prematurity, glaucoma and diabetic retinopathy. In earlier studies the Gabor filters have received considerable attention because of the characteristics of certain cells in the visual cortex of some mammals can be defined by these filters. In addition, Gabor has shown that the representation of signals using the Gaussian functions modulated by complex exponentials is optimal in the sense of minimizing the joint uncertainty in the combined time-frequency domain. Therefore, these functions provide the best trade-off between time resolution and frequency resolution. In this thesis we propose to use Gabor filtering technique for the detection of blood vessels in retina. For retina images we used 180 different filters, with the rotation separation of 1 degree to capture for more edge information of the vessels. Different scales are also used to include edge information of the vessels. After Gabor filtering image processing methods including logarithmic normalization, morphological erosion, mask processing and thresholding are used to perform the segmentation of the detected vessels. The proposed approach is applied to retina images from publicly available databases which is the Digital Retinal Images for Vessel Extraction database (DRIVE). Manually segmented versions of these images along with masks are used for performance analysis. Receiver Operating Characteristic (ROC) Curves containing false acceptance rate (FAR) and false rejection rate (FRR) are incorporated to systematically determine a suitable threshold for reliable segmentation performance. Sensitivity, specificity, efficiency and accuracy of the retina vessels segmentation have been studied and the generated results are comparable with alternative state-of-the-art methods available in the relevant literature. The results show that the employed method produces comparable and sometimes better results than the alternative methods available in the literature. Keywords: Digital Image Processing, Gabor Filters, Detection of Blood Vessels, Edge Detection, Morphological Filters, Retinal Fundus Images

ÖZ: Günümüzde, medikal imge araştırmaları, veri edinim, depolama ve kullanma gibi alanlarda kaydedilen gelişmelerden dolayı önemli bir araştırma alanı haline gelmiştir. Tıbbi alanda, anatomik yapıların hastalığın tanımı ve teşhisi ile ilgili uygulamalar ve araçların geliştirilebilmesi için büyük çabalar ortaya konulmuştur. Göz retinasının şekil olarak yapısın incelenmesi ve tanımlanması sadece tıp alanında değil biyometrik kimlik tanımlama uygulamalarında da önemli aşamalat katedilmiştir. Retinadan hastaliğın tam olarak erken teşhis ve tespitini sağlayacak pek çok bilimsel araştırmalar yapılmıştır. Retinadaki ana kısımlar optik yuvarlak, gözbebegi ve retinadaki damarlardir. Bu kısımların incelenmesi, prematüre retinopati, glokom ve diyabetik retinopati gibi bu bölgeleri etkileyen hastalıkların analizleri ve teşhisi için yardımcı olmaktadır. İlk yapılan çalışmalarda Gabor filtreleri, bazı memelilerin görsel korteksindeki hücrelerin özelliklerinin tanınmasında başarılı olduklarından dolayı, oldukça fazla dikkat çekmişlerdi. Buna ek olarak, Gabor karmaşık üstel tarafından modüle edilmiş olan Gauss fonksiyonu tabanlı sinyallerin zaman-frekans etki alanında ortak belirsizliklerinin en aza indirerek optimal bir şekilde temsil edebildiğini göstermiştir. Bu nedenle bu fonksiyonlar zaman cözurlüğü ile frekans çözünürlüğünün en iyi şekilde dengelenmesini sağlamaktadır. Bu tezde retinadaki kan damarlarının tespiti için Gabor filtreleme tekniği kullanmayı öneriyoruz. Retina imgelerine ait etkin bilgileri sağlayabilmek için yüksek frekanslı kenar kısımlardan bu bilgileri edinelbilmek doğrultusunda dönel 1 derece ayrimli vi 180 değişik filitre kullandık. Farklı ölçekleri de damarların kenar bilgilerini dahil etmek kullanılmıştır. Gabor filitre yöntemi uygulamasından sonra logaritmik düzgeleme, morfolojik erozyon, maskeleme ve eşikleme asamaları damarların bölütlenmesinin gerçekleştirilmesi için kullanılmıştır. Önerilen yöntem, kamuya açık retina bilgileri ile oluşturulmuş sayısal retina görüntü damar çıkarımı (DRIVE) veri tabanına bulunan retina imgelerine uygulanmıştır. Kullanılan retina imgelerine ait manuel olarak bölütlenmiş versiyonları da performans analizi süreçlerinde kullanılmıştır. Yanlış kabul oranı (FAR) ve yanlış red oranı (FRR) içeren alıcı çalışma karakteristiği (ROC) eğrileri sistematik güvenilir bölümleme performansı çalışmasına yönelik olarak uygun bir eşik belirlemek için dahil edilmiştir. Duyarlılık, özgüllük, verimlilik ve retina damarlarının bölümleme doğruluğu çalışılmış ve elde edilen sonuçlar ilgili literatürde mevcut alternatif yöntemlerle karşılaştırılmıştır. Sonuçlar, kullanılan yöntemin, literatürde mevcut olan alternatif yöntemler ile karşılaştırılabilir ve bazen de daha iyi sonuçlar verdiğini göstermektedir. Anahtar Kelimeler: Dijital görüntü işleme, Gabor filtreleri, kan damarlarının sezimi, kenar sezimi, morfolojik filtreler, retinal fundus imgeleri.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2013. Supervisor: Asooc. Prof. Dr. Hasan Demirel.
Keywords: Electrical and Electronic Engineering; Computer vision - Face Recognition; Image processing - Digital techniques; Digital Image Processing; Gabor Filters; Detection of Blood Vessels; Edge Detection; Morphological Filters; Retinal Fundus Images